A new motion detection algorithm based on Σ– Δ background estimation - Manzanera, Antoine; Richefeu, Julien C. (Pattern recognition letters, 2007)
Motion detection using a stationary camera can be done by estimating the static scene (background). In that purpose, we propose a new method based on a simple recursive non linear operator, the Σ– Δ filter. Used along with a spatiotemporal regularization algorithm, it allows robust, computationally efficient and accurate motion detection. To deal with complex scenes containing a wide range of motion models with very different time constants, we propose a generalization of the basic model to multiple Σ– Δ estimation.